The bog beast - Potter, Ellen, 1963- (Potter, Ellen, 1963- Big Foot and Little Foot, 2021)
On Bimbling Day, when young Sasquatches hope to earn the right to explore the North Woods on their own, Hugo, Boone, and Gigi become stranded and encounter strange and mysterious creatures.